The role of London airports in providing connectivity for the UK: regional dependence on foreign hubs - Suau-Sanchez, Pere; Voltes-Dorta, Augusto; Rodríguez-Déniz, Héctor (Elsevier, 2014)
In a context of ongoing debate about the future UK aviation policy and its implications for regional economic development, this paper discusses the role of London Heathrow and the South East airports in providing connectivity for the UK, with particular focus on the international markets that originate from regional UK airports. Using an MIDT dataset of worldwide passenger itineraries served by the European airport network during May 2013, we first establish whether London Heathrow can currently be considered the most important hub for the UK, in terms of traffic generation, connectivity, and centrality, while also measuring the dependence of UK regions on foreign airports and airlines to remain connected with the rest of the world. Results show that, despite the competition, London Heathrow benefits from its massive traffic generation to remain the most central gateway for overall UK air transport markets. However, when only regional markets are considered, significant dependence on foreign hubs appears in many destinations, particularly to Asia–Pacific or the BRIC countries where above 80% of passengers use transfer flights. These results fit nicely with the observed trends of seat de-concentration and hub-bypassing in the airline industry. While dependence on foreign hubs can be interpreted as a sign of vulnerability, there is also the argument that bypassing Heathrow allows regional airports to develop new markets and reduce the level of congestion in the London airport system.
Keywords: Airport policy; Hub competition; Regional airports; Connectivity